Letter (copy) : Wencaslao Carrillo - Tewson, Vincent
026-0024-001 International. EAB. 14th August 1939. Mr. Thomas McKenna, O.B.E., International Metalworkers' Federation, 93, Borough Road West, MIDDLESBROUGH. Dear Mr. McKenna, WENCASLAO CARRILLO. Many thanks for your letter of the 12th instant, stating that you have not received any acknowledgement of your letter of the 31st July. We have looked up our records and find that we wrote to you on the 2nd August, and for your information we are enclosing a copy of that letter. We regret that we have not yet received any intimation from the Home Office as to whether or not they are prepared to grant the necessary visas to enable Comrade Carrillo's two children to come to this country, but we will get in touch with them again to see whether it is possible for the matter to be speeded up. We will not fail to keep you informed of developments. Yours sincerely, Assistant Secretary. 292/946/26/24